2014
DOI: 10.1007/s12355-014-0341-2
|View full text |Cite
|
Sign up to set email alerts
|

CaneDES: A Web-Based Expert System for Disorder Diagnosis in Sugarcane

Abstract: Sugarcane being a long duration crop of 10-18 months faces many biotic and abiotic stresses which causes heavy losses in cane production and productivity. Timely and accurate diagnosis, of disorders that appear in crop due to these stresses, is required to reduce the losses. Paper illustrates CaneDES, an expert system to diagnose disorders in sugarcane caused by various biotic and abiotic stresses. It is a web based system available in both Hindi and English languages with remote accessibility to sugarcane far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
(32 reference statements)
0
2
0
4
Order By: Relevance
“…Algumas propostas tentaram evitar essas limitações levando em consideração tantas desordens quanto possível [83,87,88,99,100,113,115,120,127], cobrindo assim mais casos desafiadores. Isto melhora a atratividade do sistema, mas torna seu desenvolvimento muito mais complicado.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Algumas propostas tentaram evitar essas limitações levando em consideração tantas desordens quanto possível [83,87,88,99,100,113,115,120,127], cobrindo assim mais casos desafiadores. Isto melhora a atratividade do sistema, mas torna seu desenvolvimento muito mais complicado.…”
Section: Discussionunclassified
“…De fato, muito autores afirmaram que suas propostas teriam bom potencial educacional [16,25,29,34,37,61,72,89,98,102,113,123]. Por outro lado, apenas alguns poucos testaram seus sistemas em campo, ou mesmo consideraram uma aplicação prática [20,100,121,127]. As falhas técnicas mencionadas anteriormente estão certamente entre as principais razões para a baixa adoção de sistemas especialistas no campo, mas há vários outros fatores que contribuem para agravar a situação, como discutido nos próximos parágrafos.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…However, these studies cannot detect the types of diseases that have never been encountered but are found in other areas. One example is the expert system that has been studied by Hasan (2014) named CaneDES, although it has advantages in the visualization of symptoms and variations in the detection of pests and diseases but the system cannot be used to detect sugar cane diseases in Indonesia at this time [2]. Defining the disease to be detected is very important to do before designing the knowledge base in an expert system.…”
Section: Introductionmentioning
confidence: 99%